Students Perspective of Pronunciation in English as Foreign Language (EFL) Classroom - Aboe, Roswita M; Anwar, Indry Widyasti; Thalib, Syamsul Bachri; Bundu, Patta (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2023)
In pronunciation class, students encountered problems in pronouncing specific words. The problems students faced are mostly found in practicing and drilling segmental and suprasegmental words. This research intended to find out difficulties that students experienced in studying pronunciation and their perspectives as to how the methodology of teaching this subject can improve their English articulation in English as a Foreign Language Classroom. This research employed descriptive qualitative analysis. The subjects of the research were 90 students and two (2) English teachers(lecturers).The researcher used observation, questionnaires, and interviews as data collection tools in adition to the students' specific test findings of segmental and suprasegmental aspects in a text. The results of this study demonstrated student’s perspective and better approach for teaching and mastering pronunciation Abstrak Di kelas pronunciation, mahasiswa sering mengalami masalah dalam mengucapkan kata-kata tertentu. Permasalahan yang dihadapi siswa sebagian besar pada latihan dan mengulang-ulang kata segmental dan suprasegmental. Penelitian ini bertujuan untuk mengetahui kesulitan-kesulitan yang dihadapi siswa dalam mempelajari pengucapan atau artikulasi dan perspektif mereka mengenai bagaimana metodologi pengajaran mata pelajaran ini dapat meningkatkan artikulasi bahasa Inggris mereka di Kelas Bahasa Inggris sebagai Bahasa Asing. Penelitian ini menggunakan analisis deskriptif kualitatif. Subjek penelitian adalah 90 siswa dan dua (2) orang Guru Bahasa Inggris (dosen). Peneliti menggunakan observasi, angket, dan wawancara sebagai alat pengumpulan data selain temuan tes khusus siswa pada aspek segmental dan supra segmental dalam suatu teks. Hasil penelitian ini menunjukkan pandangan mahasiswa serta pendekatan yang lebih efektif untuk mengajar dan menguasai pengucapan.